2014
DOI: 10.1039/c4tx00036f
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of arsenite and thio-DMAV after long-term (21 days) incubation of human urothelial cells: cytotoxicity, genotoxicity and epigenetics

Abstract: This study aims to further mechanistically understand toxic modes of action after chronic arsenic species exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…Thio-DMA(V) showed no genotoxic mode of action in lung cells (Bartel et al 2011), but DNA damage and changes in gene expression were observed in bladder cells exposed to this compound (Naranmandura et al 2011); most recently a disturbance of the cellular damage response in DNA-damaged bladder cells was observed at sub-cytotoxic levels (Ebert et al 2014). Epigenetic effects from longterm exposure to thio-DMA(V) have also been observed at low picomolar levels (Unterberg et al 2014). …”
Section: 0 Toxicitymentioning
confidence: 99%
“…Thio-DMA(V) showed no genotoxic mode of action in lung cells (Bartel et al 2011), but DNA damage and changes in gene expression were observed in bladder cells exposed to this compound (Naranmandura et al 2011); most recently a disturbance of the cellular damage response in DNA-damaged bladder cells was observed at sub-cytotoxic levels (Ebert et al 2014). Epigenetic effects from longterm exposure to thio-DMA(V) have also been observed at low picomolar levels (Unterberg et al 2014). …”
Section: 0 Toxicitymentioning
confidence: 99%
“…Thio-DMA V has been observed as a product of both iAs and AsSugar metabolism. , Considerable toxicity from thio-DMA V has been witnessed in skin, bladder, liver, and lung cells, which is partly linked to its extreme cellular bioavailability. Thio-DMA V has been proven to generate ROS in healthy cells and to disturb cellular stress response, even at picomolar levels, in oxidatively stressed cells. Thio-DMA V exhibited no genotoxic mode of action in lung cells, but DNA injury and alterations in gene expression were witnessed in bladder cells exposed to such species . Epigenetic effects from long-term exposure to thio-DMA V have also been detected at low picomolar levels …”
Section: Metabolic Transformation and Toxicity Of Arsenicmentioning
confidence: 99%
“…176 Epigenetic effects from long-term exposure to thio-DMA V have also been detected at low picomolar levels. 180 2.7. Arsenosugars (AsSugars).…”
Section: Metabolic Transformation and Toxicitymentioning
confidence: 99%
“…It is already known that DMA 5+ is the major human urinary metabolite following both inorganic arsenic exposure and dietary arsenosugar exposure [ 32 ]; the literature implies perhaps the same premise for thio-DMA and possibly other thio-arsenicals being metabolites following both inorganic exposure or dietary arsenosugar exposure. This will be of some concern as toxicological studies have shown thio-DMA to be genotoxic, cytotoxic and as toxic or more cytotoxic than arsenite in studies with rats [ 33 , 34 ], human bladder cells [ 23 , 35 , 36 ] and human lung cells [ 37 , 38 , 39 ], with one study describing thio-DMA as “one of the most toxicologically potent arsenic species, relevant to arsenic induced carcinogenicity” [ 23 ].…”
Section: Introductionmentioning
confidence: 99%